Поширення Cоlchicum autumnale L. in situ та еx situ в Україні - Gnatiuk, A.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
Data on distribution Colchicum autumnale L. in the nature and culture are resulted. It is pointed on perspectives of conservation of this rare species in Ukraine, its reproduction and cultivation.